Polemic of Illegal Foreign Workers in Indonesia - Adelin Yovita Egia; Asrul Anggara Siregar; Muhammad Riyando Frezy (LEGAL BRIEF, 2021)
Every human being has fundamental rights in the form of a decent living, one of which can be obtained by getting a decent job; for a job that is deemed worthy, everyone must try in various ways that are legal and legal, following applicable laws and norms. Problems regarding employment are not only felt domestically, but many countries in the world are experiencing employment problems in the form of uneven employment opportunities resulting in new situations, namely, to overcome this with advanced technology, as well as information that migrates both to find work and start a life. A new one which is more worthy than the last place. This causes many migrant workers to spread worldwide, both Indonesian citizens who become foreign workers in other countries and foreigners who become foreign workers in Indonesia. The phenomenon of the current workforce has become the attention of the Indonesian people; this is caused by foreign workers entering Indonesia; it can be said that the entry of foreign workers causes social jealousy of the community. Apart from the existence of social jealousy in society, the phenomenon of foreign workers also raises another problem, namely the security of the state, which is felt to be the possibility of foreign workers. There are many factors and influences on the number of illegal foreign workers in Indonesia.